Prior trauma exposure, posttraumatic stress symptoms, and COVID-19 vaccine hesitancy. (July 2022) - Nishimi, Kristen; Borsari, Brian; Tripp, Paige; Jiha, Ahmad; Dolsen, Emily A.; Woolley, Joshua D.; Neylan, Thomas C.; O'Donovan, Aoife
Abstract: Understanding correlates of COVID-19 vaccine intentions is critical for increasing vaccine uptake. Given associations of trauma exposure and posttraumatic stress disorder (PTSD) with alterations in threat sensitivity and health behaviors, we hypothesized they could influence COVID-19 vaccine acceptance and hesitancy and be important variables to consider in the design of vaccination campaigns. Data came from a longitudinal online study of 544 US adults with high levels of pre-pandemic trauma and PTSD, assessed in August/September 2020 and March/April 2021. Individuals reported socio-demographic factors, pandemic factors, lifetime trauma history and PTSD symptoms, and COVID-19 vaccinations or intentions. We estimated bivariate associations between socio-demographics, pandemic factors, and trauma and PTSD symptoms at baseline and follow-up with COVID-19 vaccine acceptance versus hesitancy (i.e., vaccinated against COVID-19 or willing to get vaccinated versus unsure or unwilling to get vaccinated) six months later. Multiple socio-demographics (e.g., race/ethnicity, income, education, political preference) and pandemic factors (e.g., perceived likelihood of infection, household COVID-19 infection) were associated with COVID-19 vaccine hesitancy (27.2% were hesitant). However, trauma history, PTSD symptoms, and other mental health factors were not associated with COVID-19 vaccine acceptance versus hesitancy. Socio-demographic and pandemic-related factors appear more important than trauma or mental health for understanding COVID-19 vaccine intentions.